2006
DOI: 10.1597/05-023
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Computed Tomographic Analysis of the Cervical Spine in Unoperated Infants with Cleft Lip and Palate

Abstract: There was evidence for subtle upper spinal anomalies in the infant cleft lip and palate population. Our finding of reduced size of some cervical vertebral bodies may reflect delayed upper spinal development in infants with cleft lip and palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
3
32
1
2
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] In this study, the occurrence of types of CVA in subjects with TMD was investigated and compared with the occurrence of CVA in a control group without TMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10][11][12] In this study, the occurrence of types of CVA in subjects with TMD was investigated and compared with the occurrence of CVA in a control group without TMD.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several dental and skeletal malocclusions, as well as some congenital anomalies, have been related to anomalies of the cervical vertebral column. [4][5][6][7][8][9][10][11][12] On the other hand, it has been reported that variations of cervical column morphology also occur in healthy subjects with neutral occlusion and normal craniofacial morphology. 11 In our study, the control group was obtained from an orthodontic population to avoid any additional radiographic exposure to subjects as lateral cephalometric radiograph is a routine procedure required for orthodontic treatment planning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otros reportan variaciones anatómicas en cuanto a la formación de la columna cervical, cuando se comparan con niños que no presentan ningún tipo de malformación (3). Estudios realizados por el grupo de Baccetti, Franchi y McNamara muestran que es importante un diagnóstico previo del estado de maduración ósea para tomar la decisión de iniciar la intervención de algunas maloclusiones importantes, como las clases II y III esqueléticas.…”
Section: Introductionunclassified